Investigation of nutrition risk in community living adults aged 75 years and older : prevalence and associated physical health factors : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Nutrition and Dietetics, Massey University, Albany, New Zealand - Williams, Vicki Jean (Massey University, 2016)
Background: New Zealand’s population is ageing. Given prevalence of functional disability and chronic disease increases with age, and older adults account for one third of health loss in New Zealand, supporting older adults to maintain independence is paramount to reducing future health care costs. A compromised nutritional status, and declining muscle mass, strength and function threatens independence. This study aims to investigate the prevalence of nutrition risk, and identify associated socio-demographic and physical health factors among community-living older adults aged 75 years and older. Methods: A total of 200 participants were recruited from eligible patients enrolled at the Henderson Medical Centre. Baseline sociodemographic, and health information was collected using an interview style questionnaire. Body composition, including muscle mass was estimated using Bioimpedance Analysis (BIA). Muscle strength was assessed using a hand held dynamometer to measure grip strength, and a Five Times Sit To Stand (5TSTS) test. Lower extremity function performance was assessed using 2.4 meter gait speed. Validated screening tools identified nutrition status (Mini Nutritional Assessment Short Form MNA-SF), swallowing status (10 item Eating Assessment Tool EAT-10), and cognitive status (Montreal Cognitive Assessment MoCA). Pearson’s Coefficient Correlations were used to identify associations between nutrition risk and physical health nutrition risk factors. Results: The study sample (n= 200) included 89 (44.5%) men, and 111 (55.5%) women with a mean age of 80.5 years. The MNA-SF identified 2 (1%) malnourished participants, and 24 (12%) participants at risk of malnutrition. MNA-SF scores were positively correlated with a lower BMI (r=0.257, p=<0.001), lower muscle mass, lower calf circumference (r=0.333, p=<0.001), lower percentage of body fat (r=0.287, p=<0.001), and weaker grip strength (r=0.143, p=0.047). MNA-SF scores had an inverse correlation with EAT-10 scores indicating dysphagia risk (r=0.182, p=<0.010). Conclusion: A low prevalence of malnutrition was found in this study population. Those at risk of malnutrition or malnourished were more likely to use support services, be at risk of dysphagia, have a low BMI, low muscle mass, a lower calf circumference, lower percentage of body fat, and poor muscle strength. Routine nutrition risk screening is recommended to identify at risk individuals early to prevent escalation to malnutrition and poor health. Key words: Malnutrition, MNA-SF, Older Adults, Community, Dysphagia, Muscle Mass
Content removed from thesis for copyright reasons: Appendix G. Nasreddine, Z. Montreal Cognitive Assessment (MoCA). Retrieved from http://www.mocatest.org/. Appendix H. Nasreddine, Z. (2004). Montreal Cognitive Assessment (MoCA) : administration and scoring instructions. Retrieved from http://www.mocatest.org/
Keywords: Older people; Nutrition; New Zealand; Malnutrition; MNA-SF; Older adults; Community; Dysphagia; Muscle mass